A case of Leptospirosis (Journal of Dhaka National Medical College & Hospital, 2022)
We describe a case of a patient with fever and jaundice initially diagnosed as a case of dengue with viral hepatitis, but his occupation, persistence of fever and jaundice, subconjunctival hemorrhage and renal involvement provide the clue to diagnose the case as Leptospirosis.J. Dhaka National Med. Coll. Hos. 2022; 28 (01): 46-47